The economic effects of money laundering and the role of banking service in combat it: a prospective study of a sample (Journal of Accounting and Financial Studies ( JAFS ), 2014)
Money laundering is consider a crime in legal perspective and aphenomenon of negative effects in economic and Social perspective for thevarious countries of the world by the diversity of their economies to make thebadly damaged in the banking service and its reputation in some cases may leadto bankruptcy of banks, and the fact that banks is one of the most importantcircles that revolve the illicit funds, Due to its branched the banking operations,speed and overlap and increase it's complicated with the progress of bankingoperations and the use of electronic services modern here's challenges atvarious levels between the application of the legislation to combat moneylaundering and between actual fact it must find ways and means of legislativeand applied to combat this phenomenon So it must find ways and means oflegislative and applied to combat this phenomenon, so the goal of research toindicate the role of banks as a spearhead in the face of this dangerousphenomenon in order to protect themselves from financial risk and legalliability which requires the monetary authorities represented by central banksand commercial banks that to apply measures and procedures to combat thisphenomenon.The study concluded that there is a commitment by the banks to refusethe research sample for the customer to open an account or engage in anybanking operation in the case of non-completeness of the measures identifiedand that the banks applying precautionary measures Anti-money launderingwell and that these measures do not cause obstruction of the work, as well asthe need to strengthen international cooperation in this area.